ANALYSIS OF FACTORS INFLUENCING PRODUCTION AND ALLOCATIVE EFFICIENCY OF RED CHILI IN BANYUPUTIH DISTRICT, SITUBONDO DISTRICT - Prasetyo, Yudho; Puryantoro, Puryantoro; Suryaningsih, Yasmini (Universitas Galuh, 2023)
The aims of this study were (1) to analyze the factors that influence cayenne pepper production and (2) allocative efficiency of cayenne pepper production in Banyuputih District, Situbondo Regency. The research was conducted on farmers who are members of the prima donna farmer group with a population of 88 farmers. The sample used was 44 respondents who were determined by the Stratified Random Sampling technique with the area of land used by farmers. Data collected through observation, interviews and questionnaires were analyzed using the coob douglas production function and allocative efficiency analysis. Factors that influence the production of red bird's eye chilies are partially influenced by variables of land area, urea fertilizer, Phonska fertilizer, Za fertilizer and labor. While simultaneously all variables have a significant effect on the production of red bird's eye chilies. The use of production factors for seeds, phonska fertilizer, pesticides and labor is not efficient, while for land area, urea and Za fertilizers are not efficient